Uncertainty and the Reform of Elementary Math Education. (28th March 2013) - Melville, Wayne; Kajander, Ann; Kerr, Donald; Holm, Jennifer
Abstract : This paper investigates the notion of uncertainty as elementary teachers engage in conversations intended to develop their understanding and implementation of reform-based mathematics teaching. Using a narrative methodology, several sources of teacher uncertainty are investigated: teaching and learning, the subject, and improving one's own teaching. The data analysis indicates two important findings. The first is the importance of substantive and syntactic subject knowledge as a necessary foundation for teachers to understand uncertainty in terms that renew their classroom practice. The second is the need to develop and sustain communities in which teachers value opportunities to critique their classroom practices.